1989
DOI: 10.1097/00003446-198910000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Superiority of the Goodwin Procedure Over the Traditional Procedure in Measuring the Loudness Level of Tinnitus

Abstract: The results of two procedures for measuring the loudness level of tinnitus will be presented. The traditional procedure yielded significantly smaller loudness matches, when expressed in decibel sensation level (i.e., dB SL), than did the Goodwin procedure. The Goodwin procedure is more sensitive to pharmacologically induced changes in tinnitus loudness than is the traditional procedure. The Goodwin method correlates well with changes in patient's subjective rating of tinnitus severity. The Goodwin match has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
(8 reference statements)
1
6
0
1
Order By: Relevance
“…They noted modest improvement in the correlations when these measures were converted to PLUs, which took into account individual loudness growth. Risey et al (1989) showed that loudness matches at 1 kHz were significantly correlated with tinnitus severity ratings, whereas those at the tinnitus frequency were not. The size of the correlations at 1 kHz were r = .224 in linear regression analysis and r = .458 when curvilinear regression was used .…”
Section: Relating Psychoacoustic Measures To Tinnitus Severity and Ha...mentioning
confidence: 94%
See 1 more Smart Citation
“…They noted modest improvement in the correlations when these measures were converted to PLUs, which took into account individual loudness growth. Risey et al (1989) showed that loudness matches at 1 kHz were significantly correlated with tinnitus severity ratings, whereas those at the tinnitus frequency were not. The size of the correlations at 1 kHz were r = .224 in linear regression analysis and r = .458 when curvilinear regression was used .…”
Section: Relating Psychoacoustic Measures To Tinnitus Severity and Ha...mentioning
confidence: 94%
“…She concluded that, for most patients, tinnitus loudness is not "paradoxical" in that it mimics the loudness of external high-frequency tones. Risey et al (1989) emphasized the importance of a loudness match procedure from which results would correlate with self-reported loudness and severity scales . They obtained loudness matches at the tinnitus frequency and at 1 kHz.…”
Section: Tinnitus Loudness Matchingmentioning
confidence: 99%
“…A total of 4995 questionnaires with sufficient and valid data were returned. The age range of the sample was 16…”
Section: Data Collection and Samplementioning
confidence: 99%
“…Different techniques exist, such as numeric rating scales (eg, the patient is asked to rate signal intensity between 0 [scarcely perceivable] and 10 [maximum loudness]) or visual analog scales. Previous studies [15][16][17][18][19] have consistently shown that the correlation between psychoacoustic and self-rated measures of tinnitus loudness is low to moderate. However, rating scales have the advantage of reflecting the patient's personal perception, and it was shown that they are sensitive to change when used in treatment studies.…”
mentioning
confidence: 96%
“…Diversos estudos têm demonstrado que não tem sido possível estabelecer uma correlação consistente entre a medida do loudness e o grau de incô-modo (severidade) do zumbido percebido pelo paciente 16,17,26 . Alguns autores encontraram correlações fracas ou moderadas entre o loudness e o grau de incômodo do zumbido 15,30 . Pôde-se verificar que a maioria dos pacientes apresentou zumbido bilateral constante, com loudness coincidindo com o limiar de audibilidade, semelhante aos achados da literatura pesquisada.…”
unclassified